KONSTITUSIONALITAS HAK ANGKET DEWAN PERWAKILAN RAKYAT TERHADAP KOMISI PEMBERANTASAN KORUPSI - Ariya Zurnetti, Roni Efendi (Fakultas Hukum Universitas Tamansiswa Padang, 2018)
The right of inquiry is the authority of the People's Legislative Assembly (DPR) which was first regulated in the provisions of Article 70 of the Provisional Constitution of 1950. The controversy over the DPR's inquiry rights to the KPK arises because of differences in perspectives in interpreting the rights of the questionnaire. theories and norms built on philosophical and normative grounds. These different points of view lead to a different conclusion. Related to the Right of Questionnaire as one of the rights possessed by the DPR, this right is inherent in the function or position of the DPR. Therefore, the right of the questionnaire is said to be an institutional right or institutional right. Functions and rights (DPR) like two sides of a coin (two sides of one coin) can be distinguished but are inseparable.